GE_GERICHTE C/10617/2010 vom 4. September 2012 - GE Cour de justice (2012)
AUTORITÉ PARENTALE; GARDE ALTERNÉE; VISITE; CURATELLE; OBLIGATION D'ENTRETIEN; RECOURS JOINT | CC.276; CC.285.1; CC.133; CC.308.2